Determinants of Inflation in the Islamic Republic of Iran : A Macroeconomic Analysis - Liu, O. (IMF Working Papers; Working Paper ;, 2000)
This study establishes a framework for analyzing the major determinants of inflation in the Islamic Republic of Iran. An empirical model was estimated by taking into consideration disequilibria in the markets for money, foreign exchange, and goods. Results strongly support the need for a sustained prudent monetary policy in order to reduce inflation and stabilize the foreign exchange market. The estimation shows that an excess money supply generates an increase in the rate of inflation that, in turn, intensifies asset substitution (from money to foreign exchange), thereby weakening real demand for money and exerting pressures on the foreign exchange market. The study also found that a permanent rise in real income tends to increase the real demand for money and reduces inflation in the long run.